ERROR ANALYSIS ON USING SIMPLE PAST TENSE IN DIARY WRITING MADE BY EFL STUDENTS - Fitri - Apriyanti; Rahmi Aulia Nurdini (Globish: An English-Indonesian Journal for English, Education, and Culture, 2021)
This research is intended to analyze the simple past tense in writing diary writing made by EFL students. There are four certain major language skills in English that should be learned by students. Those are speaking, writing, reading and listening. In this research, the writer uses descriptive method. The data for this research was taken from the EFL’s students tasks who were asked to write a diary writing. The collected data was identified, classified, analyzed and interpreted based on the types of errors using theory corder’s were 75 errors. The finding revealed that there are 4 types of errors. They are omission, addition, selection, and ordering. Selection was the dominant errors with 30 errors (40%), followed by ordering with 16 errors (21%), addition with 15 errors (20%), and the last was omission with 14 errors (19%). Based on the data analysis above, the most of students’ errors was selection and the least of students’ errors was omission.